Prophylactic Treatment of Pediatric Migraine: Is There Anything New in the Last Decade? - Papetti, Laura; Ursitti, Fabiana; Moavero, Romina; Ferilli, Michela Ada Noris; Sforza, Giorgia; Tarantino, Samuela; Vigevano, Federico; Valeriani, Massimiliano (Frontiers in Neurology, 2019)
Migraine is a frequent and very disabling disease pediatric age. Despite this, there is a lack of controlled studies on the pharmacological treatment of primary headaches in the developmental age. Given that the recently introduced calcitonin gene-related peptide (CGRP) inhibitors (CGRP-r) are still limited to adulthood, there is no drug with exclusive indication for migraine treatment in pediatric age. This raises several limitations in terms of adherence and effectiveness of the therapy. Moreover, the scenario is complicated by placebo response, which is larger in children and adolescents than in adults and often leads to an improvement in the attack frequency even in absence of any active pharmacological treatment. Our goal was to investigate the real evidence concerning the prophylactic therapy of pediatric migraine by reviewing the clinical studies published between 2010 and 2019.